Uveitis and blindness in a closed herd of Equidae following leptospiral infection - Gerras, J.; Young, K.; Roberts, D.; Waldman, G.; Salmon, J. H.; Gilger, B. C. (Frontiers in Veterinary Science, 2025)
ObjectiveTo describe the ocular findings, chronology of disease, and serum leptospiral titers in a group of horses, mules, and donkeys following an outbreak of leptospirosis.MethodsFifty Equidae in central North Carolina had ophthalmic examinations and serum leptospiral microscopic agglutination test (MAT) titers performed every 3–6 months for 24 months followed by a final examination at 34 months.ResultsThroughout the nearly three-year study period, 17 horses (34%; 17/49 horses) developed signs of uveitis; 20 eyes (20/34; 58.8%) of these 17 horses were visual at the initial examination, but only four eyes (11.8%) remained visual at the final examination. Serum titers (serogroups Pomona and Bratislava) in horses with uveitis were significantly elevated compared to Equidae without uveitis (p < 0.02). In the 32 horses, donkeys, and mules that did not develop uveitis, a subgroup of 11 horses and one donkey had negative or low serum leptospiral titers (titers ≤1:800) while a second subgroup of 16 horses, three mules, and one donkey had high leptospiral titers (>1:800) but never developed uveitis. Water sources in the pasture were found to have high levels of leptospira.ConclusionApproximately 1/3 of horses on a farm exposed to Leptospira developed uveitis and blindness. Serum titers to L. Pomona and L. Bratislava were significantly elevated in horses with uveitis. However, despite exposure, some horses, even with very high serum titers, never developed ocular disease. These data indicates that further research is warranted to investigate the genetic and immunological aspects of the pathogenesis and susceptibility of leptospiral-associated uveitis.